ONLINE GAMES AS THE MEDIA BEFORE HAVING EFL TEST (TOEFL EQUIVALENCE) FOR THE TWELFTH STUDENTS OF SMA NEGERI I JOMBANG 2018/2019 - Semani, Semani (STKIP PGRI Jombang, 2019)
English is one of the compulsory subject for Senior High School. It is taught for two hours in a week. The students feel that the time is not enough for them because they must face national examination for it. SMA Negeri I JombangÂ has done additional course and joint with ITS language Center for Having EFL Test to measure the studentsâ€™ ability in English. Before conductingÂ the test, the teacher prepares them by using online game to make them familiar with English. After implementing it, the TOEFL Score/ EFL Test Score makes us satisfied. It is proved by there are more than 20 students of 36 students get more than 450.